Leptin secretion and leptin receptor in the human stomach. Issue 2 (1st August 2000) - Sobhani, I; Bado, A; Vissuzaine, C; Buyse, M; Kermorgant, S; Laigneau, J-P; Attoub, S; Lehy, T; Henin, D; Mignon, M; Lewin, M J M
Abstract : BACKGROUND AND AIM: The circulating peptide leptin produced by fat cells acts on central receptors to control food intake and body weight homeostasis. Contrary to initial reports, leptin expression has also been detected in the human placenta, muscles, and recently, in rat gastric chief cells. Here we investigate the possible presence of leptin and leptin receptor in the human stomach. METHODS: Leptin and leptin receptor expression were assessed by immunohistochemistry, reverse transcriptase-polymerase chain reaction (RT-PCR), and western blot analysis on biopsy samples from 24 normal individuals. Fourteen (10 healthy volunteers and four patients with non-ulcer dyspepsia and normal gastric mucosa histology) were analysed for gastric secretions. Plasma and fundic mucosa leptin content was determined by radioimmunoassay. RESULTS: In fundic biopsies from normal individuals, immunoreactive leptin cells were found in the lower half of the fundic glands. mRNA encoding ob protein was detected in the corpus of the human stomach. The amount of fundic leptin was 10.4 (3.7) ng leptin/g mucosa, as determined by radioimmunoassay. Intravenous infusions of pentagastrin or secretin caused an increase in circulating leptin levels and leptin release into the gastric juice. The leptin receptor was present in the basolateral membranes of fundic and antral gastric cells. mRNA encoding Ob-RL was detected in both the corpus and antrum, consistent with a protein of ∼120 kDa detected by immunoblotting. CONCLUSION: These data provide the first evidence of the presence of leptin and leptin receptor proteins in the human stomach and suggest that gastric epithelial cells may be direct targets for leptin. Therefore, we conclude that leptin may have a physiological role in the human stomach, although much work is required to establish this.